Specimen thickness effect on elastic-plastic constraint parameter A - G.P. Nikishkov; Yu.G. Matvienko (Fracture and Structural Integrity)
Three-dimensional elastic-plastic problems for a power-law hardening material are solved using the finite element method. Distributions of the J-integral and constraint parameter A along the crack front for varying specimen thickness and crack depth are determined for edge cracked plate, center cracked plate, three point bend and compact tension specimens. The constraint parameter A is a measure of stress field deviation from the HRR field. Higher A values signify lower specimen constraint. Results of finite element analyses show that the constraint parameter A significantly decreases when specimen thickness changes from 0.1 to 0.5 of the specimen width. Then it has more or less stable value. Among four specimen the highest constraint is demonstrated by the compact tension specimen which has the constraint parameter A lower than its small scale yielding value.